Status epidermis in introduktion of the drug «radiesse» and «luminaire» - G. M. Mogilnaya; E. V. Fomicheva; Yu. E. Blatt (Кубанский научный медицинский вестник)
Changes occurring which took place in epidermis skin after injection drugs «radiesse» and «luminaire» are analyzed in the experiment. Preparations introduced endodermal evaluation results conducted at 2, 4 and 16 weeks experiment to drug «radiesse» and at 2 and 16 weeks to drug «luminaire». Slices stained hematoxylin and eosin, by Weigert and Van-Gieson for selective detection DNA used reaction Feulgen. Distribution of total protein studied in preparations stained amido - black at pH 2.2, and cationic at pH 8.2. Spended the morphometry of cores were differentiated in layers epidermis and given assessment their optical density. It is shown that the introduction of fillers lead to increase thickness epidermis more than 1.5. The zone of germenative compartment increases mitotic activity in epithelial cells. Cells of granular layer increasing temp of protein synthesis having cationic charge. Revealed changes induced status DNA cell nuclei differentiated layers epidermis.